1989
DOI: 10.1002/ls.3010010405
|View full text |Cite
|
Sign up to set email alerts
|

The effects of engine oil additives on valve train wear

Abstract: Preventing valve train wear in automotive engines i s one of the most importantproperties of anengine oil. However, the influence of engine oil additives on valve train wear has not been suffliently clarifld. In this investigation, the antiwearperformance of additives (such as ashless dispersants, metallic detergents and zinc dithiophosphate -WTP) and the influence of the interaction of the additives were evaluated. Firstly, ashless dispersants (such as succinimides. succinic esters and benzylamine-type addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…They are also employed in gear and other industrial oils where they act as rust inhibitor and extreme-pressure additives. It has been shown by several authors that these additives can contribute to wear and scuffing control, both when used as additives in simple solution [8][9][10][11][12] and in synergistic combination with more conventional antiwear additives [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…They are also employed in gear and other industrial oils where they act as rust inhibitor and extreme-pressure additives. It has been shown by several authors that these additives can contribute to wear and scuffing control, both when used as additives in simple solution [8][9][10][11][12] and in synergistic combination with more conventional antiwear additives [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In these applications the overbased sulfonate is not used as a detergent, but rather as a rust inhibitor and extreme pressure additive [7-l0]. Over the past few decades, the antiwear properties of overbased sulfonates have been explored [11][12][13][14] and these properties were said to be related to the formation of protective films caused by the deposition of inorganic carbonate on the surface of the metal. The effect of this deposited film is analogous to the films deposited by traditional phosphorous and sulfur containing antiwear additives like ZDDP.…”
Section: Introductionmentioning
confidence: 99%
“…As a high polar additive, the detergents may actively compete with the ZDDP for the rubbing surfaces. Rounds [17] and Shirahama [27], have also shown that over-based sulfonates can retard the rate of ZDDP decomposition. Thanks to FeF 3 , which catalyzes ZDDP to decompose at lower temperature in presence of detergents.…”
Section: Zddp Detergents and Catalyst Combinationsmentioning
confidence: 98%